2021
DOI: 10.3390/genes12081277
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Exome Sequencing in Children with Suspected Isolated Hearing Loss

Abstract: Purpose: Hearing loss is characterized by an extensive genetic heterogeneity and remains a common disorder in children. Molecular diagnosis is of particular benefit in children, and permits the early identification of clinically-unrecognized hearing loss syndromes, which permits effective clinical management and follow-up, including genetic counselling. Methods: We performed whole-exome sequencing with the analysis of a panel of 189 genes associated with hearing loss in a prospective cohort of 61 children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Concerning SHL subjects, WES analysis was fundamental to highlight the molecular cause in 55% of patients. These results are in line with previous studies, from both Italian cohorts and international ones, that verified how the overall diagnostic yield in HHL patients is around 50% [ 32 , 33 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Concerning SHL subjects, WES analysis was fundamental to highlight the molecular cause in 55% of patients. These results are in line with previous studies, from both Italian cohorts and international ones, that verified how the overall diagnostic yield in HHL patients is around 50% [ 32 , 33 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among the repeated variants, there were five that had been previously described (c.2171_2174del, g.(_43890333)_(43940887_? )del in the STRC gene [ 23 , 24 ], c.11864G>A and c.12234_12235del in the USH2A gene [ 25 , 26 ], c.1001G>T in the SLC26A4 gene [ 27 , 28 ] and three that had not been previously described (c.107A>C in the SLC26A4 gene, c.2656del and c.4903A>T in the OTOF gene). Families carrying these variants were from different regions of the Russian Federation.…”
Section: Resultsmentioning
confidence: 99%
“…Their significant improvement has been possible due to advanced omics, and Table 2 summarizes the advanced genomics, transcriptomics and epigenomics techniques that have been applied in cochlear research, alongside the improvement that they have provided in the field. For instance, genome sequencing has allowed to identify new variants in genetic hearing loss and represents a great improvement in the diagnosis of genetic deafness in newborns [72][73][74]. Nonetheless, studies on the cochlea are particularly challenging compared to other sensory organs, because of several practical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of novel variants represents a fundamental step forward in the understanding of the molecular basis of cochlear diseases, and indeed it has improved the diagnosis of genetic hearing loss, as well as the prediction of its severity and prognosis. So far, a number of studies have benefitted from genome sequencing (via either WES or WGS) for early detection of hearing loss [72][73][74]. For instance, a recent study has shown that the combination of conventional hearing screening and extended genetic sequencing improves the early diagnosis of inherited hearing loss in newborns, with important implications for their clinical management [75].…”
Section: Genomic Studies Have Delivered Unprecedented Knowledge On Th...mentioning
confidence: 99%